A new insight into sugarcane biorefineries with fossil fuel co-combustion: Techno-economic analysis and life cycle assessment. (1st June 2018) - Mandegari, Mohsen; Farzad, Somayeh; Görgens, Johann F.
Graphical abstract: Highlights: Techno-economic and environmental study of biorefineries annexed to sugar mill. Study the self-energy sufficient and fossil fuel co-combusting biorefineries. Lactic acid, ethanol and methanol are the most feasible products respectively. Improvements in agrochemical utilisation leads to overall environmental savings. Methanol biorefineries performed poorly across most of the impact categories. Abstract: In this study, alternative lignocellulosic biorefineries annexed to a typical sugarcane mill were investigated, to produce ethanol, lactic acid or methanol, or co-production of ethanol and lactic acid, all with surplus electricity for sale by conversion of sugarcane bagasse and harvesting residues (brown leaves) as accessible feedstock. In order to meet the energy demand of the sugar mill and biorefinery, burning a portion of feedstock or fossil source (coal) along with residues in the centralized combined heat and power unit were assumed as energy supplement strategies. A thorough Aspen Plus simulation was developed for each biorefinery scenario considering all required process units and supplementary units (i.e. combined heat and power, waste water treatment and evaporation). Furthermore, mass and energy balances along with costing data were applied to carry out techno-economic analysis, Monte Carlo finical risk study and life cycle assessment, in a multi-criteria desirability matrix. The lactic acid production biorefinery was found to be the most energy intensive process with highest chemical consumption and the highest conversion of biomass carbon input to products. Consumption of coal as an alternative source of energy enhanced the available biomass for valorization. Biorefineries with coal combustion producing ethanol or ethanol-lactic acid showed better environmental performance than methanol producing biorefineries, based on 1 ton of product. Although, the co-production of ethanol and lactic acid showed the largest likelihood of economic success, Methanol producing scenarios had a zero likelihood of an economic viability without substantial financial incentives or enhanced market prices.